New records of Asteraceae for the non-native flora of Tunisia and north Africa with some nomenclatural remarks - El Mokni, Ridha; Iamonico, Duilio; Véla, Errol; Verloove, Filip; Domina, Gianniantonio (Mediterranean Botany, 2022)
Sixteen new Asteraceae are added to the non-indigenous flora of Tunisia. Six of them (Dimorphotheca ecklonis, Gaillardia pulchella, Gazania linearis var. linearis, Guizotia abyssinica, Rudbeckia triloba and Tithonia diversifolia) are also new for the flora of North Africa. Chrysanthemum morifolium is here first reported for the Mediterranean Basin. Seven genera (Argyranthemum, Bidens, Dimorphotheca, Gaillardia, Guizotia, Rudbeckia and Tithonia) are recorded for the first time for the vascular flora of Tunisia. Most of these species escaped from gardens and pots and became casual along roadsides and/or disturbed areas after cypsela dispersion (except for Chrysanthemum morifolium). Some species, even though appearing to be well established locally and are potentially invasive at a worldwide level, still do not behave so in Tunisia. In addition to the floristic notes, the typification of the names Dimorphotheca ecklonis, Gorteria linearis and Mirasolia diversifolia are discussed.